Meretas Praktik Pendidikan Akuntansi yang Bela Negara - Septyan, Krisno; Mintoyuwono, Danang (Jurusan Akuntansi Politeknik Negeri Malang, 2023)
Abstract: Initiating Accounting Education Practices that Defend the Nation Purpose: This study aims to show the efforts of liberating accounting education in order to show accounting attitudes that defend the country. Method: Ki Hadjar Dewantara's thinking is revealed to be a research method in an ontologically synchronic way between the researcher and the thinker. Result: Accounting for defending the state must understand its nature, which means that local culture should become the accounting standard. National hero figures can become inspirations in accounting education. Accounting education does not only meet market needs but must have wider benefits for the Indonesian people as well as evoke love for the motherland and continue the struggle of national heroes. Novelty: This research departs from the self-consciousness of researchers about state defense that exists under an institution that labels itself as a state defense institution. Contribution: The values of the Nusantara archipelago need to be part of every major course in the accounting department on stand as a separate course. Abstrak: Meretas Praktik Pendidikan Akuntansi yang Bela Negara Tujuan: Penelitian ini bertujuan menunjukkan usaha memerdekakan pendidikan akuntansi agar menunjukan sikap akuntansi yang bela negara. Metode: Pemikiran Ki Hadjar Dewantara diturunkan menjadi metode penelitian dengan cara sinkronis ontologis antara peneliti dan pemikir. Hasil: Akuntansi bela negara harus memahami di mana kodrat dirinya yang berarti budaya setempat seharusnya menjadi standar akuntansi. Tokoh pahlawan nasional juga bisa menjadi inspirasi dalam pendidikan akuntansi. Pendidikan akuntansi bukan sekadar memenuhi kebutuhan pasar tapi harus memiliki manfaat lebih luas untuk bangsa Indonesia sekaligus mengevokasi cinta tanah air serta meneruskan perjuangan para pahlawan nasional. Kebaruan: Penelitian ini berangkat dari kesadaran diri peneliti tentang bela negara yang bernaung di bawah institusi yang melabeli dirinya sebagai instusi bela negara. Kontribusi: Nilai-nilai Nusantara perlu menjadi bagian pada setiap mata kuliah utama di jurusan akuntansi tidak berdiri sebagai mata kuliah sendiri.